Open Access to Antipsychotics in State Medicaid Programs: Effect on Healthcare Resource Utilization and Costs among Patients with Serious Mental Illness - Rashmi Patel; Onur Baser; Heidi C. Waters; Daniel Huang; Leigh Morrissey; Katarzyna Rodchenko; Gabriela Samayoa (Journal of Health Economics and Outcomes Research)
# Background The restrictive consequences of Medicaid formulary restriction policies on antipsychotic medications may lead to higher healthcare utilization and costs among beneficiaries with serious mental illness (SMI).